QUEER LEARNER IDENTITY AND ENGLISH LANGUAGE LEARNING IN A THAI CONTEXT - Suebkinnon, Tinnawat; Sukying, Apisak (European Journal of English Language Teaching, 2021)
This study examined the identity construction of queer learners in English language learning and its influences on English language learning. The four participants were male, queer and studied in English majors and English language teaching in a Thai university. Two of the participants were known to the researcher. Semi-structured interviews, field notes, and a digital sound recorder were used for data collection and qualitative content analysis was used to analyze the data. The findings revealed that queer characteristics and marginalized and unequal positions based on gender identity and sexual orientation were two main factors constituting queer learner identity in English language learning. The majority of the participants shared that their queer characteristics were conducive to their speaking skills. Additionally, it was shown that the heteronormative Thai context motivated the participants to pursue English language proficiency. The participants reported that English language proficiency was advantageous for their future success and helped them gain parental and societal acceptance. Moreover, the participants stated that learning the English language would allow them to migrate to English-speaking countries that are welcoming to queer people. The results also indicated that some participants who desire a Western partner viewed English as beneficial to finding a Western man, whom they thought would be more open to gender diversity than Thai men. These findings provide a better understanding of the identity construction of queer learners and its influences on English language learning. Article visualizations: